Best Practices in Education: Responsibly Teaching the History of Preaching (Homiletic, 2023)
A recent evaluation of the histories of preaching by Hughes Oliphant Old and O.C. Edwards, Jr. raises concerns for what students learn about the history of preaching. It also raises questions of whether or not teachers should use course materials that perpetuate racism and racial biases or if used, how those materials need to be introduced with preparatory words of caution. Whether or not these resources are used, additional resources need to be made available to students so that they may have a more realistic and expansive view of the history of preaching.